Television journalism - Cushion, Stephen; Sage eBooks (Los Angeles, [Calif.] ; London : SAGE, 2012)
An engaging and up-to-date look at television journalism examining the history, contemporary trends and future directions of the medium.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Television broadcasting of news; Electronic books